KOORDINASI PENGELOLAAN SADAR WISATA MASYARAKAT DI LOKASI OBYEK WISATA PANCUR AJI - Dwi Radial Riami E.01105095 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The title of this research is “Coordination of Management in Improving Public Tourism Awareness in Pancur Aji Resort Site”. This research is aimed to know the coordination of management which is apply by culture and tourism department of Sanggau Regency in improving public tourism awareness in Pancur aji Resort Site. There are two kinds of coordination will be used. Interdisciplinary coordination. First, unity of action in reality the coordination become blocked due to some people are more concerned with their own job. Second, create the discipline, it is because of there is no awareness to be responsible on their job that were given. Inter-related coordination have no constraints and could make it run not effective. Key Words:  Coordination of management, tourism awareness, Interdisciplinary  Coordination, Inter-related Coordination.